United Dynamics Simulation of Driving Axle Under Typical Working Condition - Mingrui Yin; Xuewei Li; Chen Jing; Zenghua Fan (Jixie chuandong)
The three-dimensional geometric model of the driving and driven bevel gear， differential transmission planetary gear and half axle gear of driving axle main reducer is established by using three-dimensional software UG， and the non-interference assembly model is obtained and the creation of virtual prototype model is completed in the dynamic software Adams by which importing into with the common Parasolid graphics interchange format. Based on the Hertz elasticity contact theory， combining with the actual working status of driving axle for a sightseeing car， the dynamics simulation analysis of the starting， straight driving， turning working conditions are achieved by selecting appropriate contact parameters and applying corresponding constraints and loads. Reliable basis for the further research on kinematics and dynamics characteristics of driving axle main reducer and differential transmission gear is provided and technical support to reduce the vibration of the drive axle main reducer and differential transmission and optimize its performance characteristic is provided.